Research landscape of PBL-STEM education: a systematic analysis review - Zhang Lei; Nur Atiqah Jalaludin; Mohamad Sattar Rasul (Intelektual Pustaka Media Utama, 2026)
The science, technology, engineering, and mathematics (STEM) education has emerged as a global education priority, many countries have printed their development strategies to national blueprints and recognized STEM education as a key role in the effective implementation of skills training in the21st-century. Project-based learning (PjBL) and problem-based learning (PrBL) or PBL is significant in cultivating students’ knowledge and skills, integrating PBL into STEM (PBL-STEM) education is a new attempt in recent years to integrate student-centered learning methods into the STEM learning process. This study aims to explore the development trends of PBL-STEM and provide recommendations to support talent cultivation in the digital era. Based on a systematic review of 1999 articles in SCOPUS database, this study uses content analysis to identify key themes in PBL-STEM. The findings indicate that the construction of student-centered PBL curriculum, the development of innovative teaching models, and interdisciplinary integration are central to the evaluation of PBL-STEM. Moreover, the integration of emerging technologies and multi-disciplinary approaches enhances STEM competency to cultivate 21st-century skills. PBL-STEM emphasize students’ higher-order abilities, positioning it as a strategic reform for future society. This study reveals the importance of curriculum innovation, instructional reform, evaluation mechanisms, and the professionalization of STEM educators are fundamental with the rapid technological advancement.